The Philosophy of Pluralism in the Neo-Albanians Development Circumstances of the 1930s - Koti, Isidor (Richtmann Publishing, 2012)
The work draws attention on the treatment of educational with pluralism, evaluating it firstly as a solution to theAlbanian problems, analyzing educational issue connected with pluralism, making evident the Neo-Albanian views as questionsand ancient responses, as well as the state and its role on the development of pluralist institutions. Generally defined, the termpluralism states institutional forms for political power (force) distribution. In order to analyze the mentioned phenomenon, itmeans to examine the power or the distributed authority in society. Very often the term pluralism is used to signify any situationwhere there are no political, ideological, cultural and ethnic ruling groups. We mean that a certain situation is characterized bythe competition existing between elites or interested groups and the pluralist society allow this competition to be freelydeveloped. In the Albanian development circumstances of the 1930s, Neo-Albanians chose the pluralism of opinions, whichwere introduced in that time publications, especially in the â€œAlbanian Attemptâ€ magazine. We could conclude that the societies,which have a stable economic development, have developed the values and the appropriate structures connected withindustrialization, such as the efficiency, rationalism, re-investments and benefit; all these create the basis for the increasing rateof the integration of social groups on the basis of pluralism as a political solution. Otherwise, the Albanian society of the 21stcentury has not secured yet these stable economic developments, the values and structures connected with it and also becauseof the fragility are the democratic system and political pluralism.